ANALISIS TEKNIK PENGERITINGAN BERGANDA PADA RAMBUT UNTUK MENINGKATKAN KETAHANAN BENTUK KERITING - Safana Zakira Athya; Helen; Nabila Amalia; Nadila Afriyanti; Asrah Rezki Fauzani; Mutia Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Hair styling is an important part of the beauty field that aims to enhance a person's appearance and self-confidence. One of the techniques commonly used in hair styling is hair curling. However, in practice, the curls often do not last long. Therefore, a curling technique that can produce longer-lasting curls is needed, one of which is the double curling technique. This study aims to analyze the application of the double hair curling technique in improving the durability of curl shapes. This research uses a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation. The study was conducted on Wednesday, March 12, 2026, at Asnah Salon, Medan Perjuangan, with the salon owner as the research subject. The results show that the double curling technique, which is carried out through two stages of curling, can produce stronger, more voluminous, and longer-lasting curls compared to the conventional single curling technique. Therefore, the double curling technique can be an alternative hair styling method to produce more durable curls.